2020
DOI: 10.1088/1741-4326/abb25c
|View full text |Cite
|
Sign up to set email alerts
|

Intense whistler-frequency emissions at the pedestal collapse in KSTAR H-mode plasmas

Abstract: The edge confinement barrier of high-confinement mode (H-mode) plasma involves a variety of plasma waves alongside with fluid instabilities and collective particle transport during the barrier collapse. We demonstrate a new method of resolving the plasma waves by measuring the modulations embedded in the second harmonic electron cyclotron emission (ECE). Utilizing mm-wave heterodyne detection and fast digitization technologies on the KSTAR tokamak, we resolve not only the frequency spectrum but the wavenumber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…On LHD, the acquisition system of the ICE measured at a dipole antenna located in the 10-O port inside the vacuum vessel was developed in partnership with KSTAR [37][38][39][40]. A fast digitizer performs direct sampling of the radiofrequency measurements at a frequency of 1.25 GSa/s.…”
Section: Ice From Lhd Deuterium Plasmas: Diagnostic Contextmentioning
confidence: 99%
“…On LHD, the acquisition system of the ICE measured at a dipole antenna located in the 10-O port inside the vacuum vessel was developed in partnership with KSTAR [37][38][39][40]. A fast digitizer performs direct sampling of the radiofrequency measurements at a frequency of 1.25 GSa/s.…”
Section: Ice From Lhd Deuterium Plasmas: Diagnostic Contextmentioning
confidence: 99%
“…Therefore, sufficient data points to perform a signal correlation analysis can be gathered using the procedure described in section 2.2. In addition, the bicoherence given hereafter measures the degree of phase coupling between the fluctuating components, which also implies a nonlinear interaction between the fluctuating components [21,23,25,26].…”
Section: Appearance Of Multiple Modes and Their Interactionmentioning
confidence: 99%
“…Additionally, this study was conducted with a correlation analysis of the ECEI data. The implementation of channel correlation analysis for ECEI measurements [21,22] has enabled research on the interaction between turbulent fluctuation and magnetic islands [23,24], flow changes, coupling of turbulent eddies due to resonant magnetic perturbation [25], and whistler-frequency emission measurement based on the estimation of the vertical wavenumber [26]. Similarly, [27] investigated the change in fluctuations during sequences of sawtooth oscillations and suggested that the growth of fluctuations results from an increase in the T e gradient owing to the heat pulse stemming from the sawtooth crash.…”
Section: Introductionmentioning
confidence: 99%
“…fast ions from neutral beam injection (NBI), fusion reactions, acceleration by ICRH waves or during edge localized modes (ELMs) crash, and runaway electrons (REs) during low density discharge and major disruption. The instabilities driven by these energetic particles have been widely studied with ICE diagnostic in many devices including JET [8], TFTR [9,10], DIII-D [3,5,[11][12][13], ASDEX Upgrade [14,15], KSTAR [16][17][18] and EAST [4] tokamaks, NSTX-U [19] spherical tokamak and LHD [20] stellarator.…”
Section: Introductionmentioning
confidence: 99%